2016
DOI: 10.1109/lawp.2015.2507938
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Dual-Band CPW-Fed Printed LPDA for Wireless Communications

Abstract: A dual-band printed Log-periodic dipole array (LPDA) antenna for wireless communications, designed on a lowcost PET substrate and implemented by inkjet-printing conductive ink, is presented. The proposed antenna can be used for wireless communications both within the UHF (2.4-2.484 GHz) and SHF (5.2-5.8 GHz) wireless frequency bands, and presents a good out-of-band rejection, without the need of stopband filters. The antenna has been designed using a general purpose 3D CAD, CST Microwave Studio, and then reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…A CPW-fed slot antenna is realized by embedding a vertical stub with the T-shaped strip and a slit to the ground plane as reported in [22] for realizing dual-band operations. Various dual-band antenna designs include symmetrically introducing four slot stubs on lateral arms [23], by an asymmetric slots in F-shaped end patch [24], by backed ground plane with radial stub on two identical elements [25], by using two parallel monopoles, one curved and one fork-shaped [26], by monopole structure with two inverted U-shaped, L-shaped lateral stubs [27], with two rectangular parasitic elements and an I-shape grounded stub [28], by printed log-periodic dipole array (LPDA) [29], by slots and monopole antenna [30], and by employing meander line technique in [31]. A theoretical and experimental study of twin-slot multilayer CPW-fed antenna is reported in [32], and highly selective behavior and regulation of sharp variations of a discontinuous parallel-plate waveguide with a narrow rectangular ridge filled with axially anisotropic material identified using mode matching technique is achieved in [33].…”
Section: Introductionmentioning
confidence: 99%
“…A CPW-fed slot antenna is realized by embedding a vertical stub with the T-shaped strip and a slit to the ground plane as reported in [22] for realizing dual-band operations. Various dual-band antenna designs include symmetrically introducing four slot stubs on lateral arms [23], by an asymmetric slots in F-shaped end patch [24], by backed ground plane with radial stub on two identical elements [25], by using two parallel monopoles, one curved and one fork-shaped [26], by monopole structure with two inverted U-shaped, L-shaped lateral stubs [27], with two rectangular parasitic elements and an I-shape grounded stub [28], by printed log-periodic dipole array (LPDA) [29], by slots and monopole antenna [30], and by employing meander line technique in [31]. A theoretical and experimental study of twin-slot multilayer CPW-fed antenna is reported in [32], and highly selective behavior and regulation of sharp variations of a discontinuous parallel-plate waveguide with a narrow rectangular ridge filled with axially anisotropic material identified using mode matching technique is achieved in [33].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the bandwidth often mixes the UHF-WLAN bands with the LTE bands [1][2][3]. Sometimes, the SHF-WLAN band may also be included [4][5][6]. For the configurations of the antennas, most of them involve the use of the meandered lines.…”
Section: Introductionmentioning
confidence: 99%
“…For the configurations of the antennas, most of them involve the use of the meandered lines. In [5,6], however, the log-periodic dipole arrays are adopted. As the lowest frequency is decreased to 690 MHz, it causes the main challenge to design the mobile antenna with an even limited space.…”
Section: Introductionmentioning
confidence: 99%
“…It is also difficult to be integrated with the printed circuit. Also, a printed LPDA antenna fed by a coplanar waveguide (CPW) is presented in [11,12]. However, these antennas are also somewhat complicated in terms of integration with other RF circuits.…”
Section: Introductionmentioning
confidence: 99%